Full data set from rock pools field study - Vass, Mate (Uppsala University, 2019)
The data set consists of environmental meteorological and geographical data, 16S and 18S OTU tables, taxonomy tables, and phylogenetic tree files for both bacteria (16S) and microeukaryotes (18S). Further, R script is provided that was used to analyze the data.

The dataset was originally published in DiVA and moved to SND in 2024.

Datauppsättningen består av miljömeteorologiska och geografiska data, 16S och 18S OTU-tabeller, taxonomitabeller och fylogenetiska trädfiler för både bakterier (16S) och mikroeukaryoter (18S). Dessutom tillhandahålls ett R-skript som användes för att analysera data.

Datasetet har ursprungligen publicerats i DiVA och flyttades över till SND 2024.
Full data set from rock pools field study
Keywords: meteorology; meteorologi; Biology with specialization in Limnology; Biologi med inriktning mot limnologi; Microbiology; Mikrobiologi